Lecturer’s Perspectives and Implementation of Translanguaging in English Education Study Program Universitas Palangka Raya - Misericordias Domini; Olga Dona Retsi (JET (Journal of English Teaching), 2026)
Translanguaging is increasingly recognized as a way to support learning in multilingual EFL classrooms, yet its concrete implementation in grammar instruction and lecturers’ perspectives in under-researched regions such as Central Kalimantan remain unclear. This study examines how translanguaging is used in an Intermediate English Grammar class at a public university and how the lecturer evaluates its role in English language teaching. Using a qualitative case study, data were collected through nonparticipant classroom observations and a semi-structured interview, then analyzed using structural and planning-based classifications of translanguaging. The findings show that translanguaging is highly patterned at the sentence level through inter-sentential, intra-sentential, insertion, and tag uses, with English maintained as the main medium of instruction. The lecturer employs brief, targeted use of Bahasa Indonesia to clarify complex grammar, scaffold understanding, and enhance engagement while keeping its proportion low. These results suggest that principled translanguaging can strengthen comprehension and participation without hindering target language development.